2020
DOI: 10.1002/pa.2476
|View full text |Cite
|
Sign up to set email alerts
|

Can Website quality Moderate the Relationship between Information‐task‐fit and Electronic word of mouth?

Abstract: Information technology expertise has comprehensively revamped and made well recognized, the hospitality and tourism industry. Electronic businesses, which are different type of commercial business was constructed and established with the help of the internet, and this now affects the way clients react. The current research seeks to explore the effect of information‐task‐fit, on electronic word of mouth (eWOM) of users of Turkish airlines. Furthermore, the present study examines the moderating role of website q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Furthermore, some studies have been consistent with this finding (Dedeke, 2016; Tarkang et al., 2020). Online reviews on e‐commerce sites are resourceful and valuable information, and consumer perception may rise (Tarkang et al., 2022). As such, to enhance consumers’ experience via a useful online review, it is important to meet the consumers’ needs and wants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some studies have been consistent with this finding (Dedeke, 2016; Tarkang et al., 2020). Online reviews on e‐commerce sites are resourceful and valuable information, and consumer perception may rise (Tarkang et al., 2022). As such, to enhance consumers’ experience via a useful online review, it is important to meet the consumers’ needs and wants.…”
Section: Discussionmentioning
confidence: 99%
“…If the electronic words-ofmouth information meets the users' task requirements, then they will regard it as useful (Leong et al, 2022). Moreover, preceding research by Tarkang et al (2020Tarkang et al ( , 2022 showed that when customers find the information they are looking for on a website and it meets their expectations, they perceive the website to be of high quality. As such, if online review information meets the demands of users, they tend to perceive that information as helpful.…”
Section: Information Task-fit and Online Review Helpfulnessmentioning
confidence: 99%